FROM REFORM TO RECONSTRUCTION: EDUCATIONAL PHILOSOPHY OF MUHAMMAD ABDUH AND MUHAMMAD IQBAL IN CONTEMPORARY ISLAMIC EDUCATION - Tajuddin Hamzah; Zuhdiyah Zuhdiyah; Maryamah Maryamah; Nyayu Soraya (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the reform and reconstruction of Islamic education through the educational thought of Muhammad Abduh and Muhammad Iqbal in the context of contemporary Islamic education. This research employs a qualitative approach using a literature review method. The data were collected from scholarly journal articles accessed through the Google Scholar database with a publication range from 2020 to 2025. Data analysis was conducted using content analysis and comparative analysis to identify the main concepts within the educational thought of both thinkers and examine their relevance to contemporary challenges in Islamic education. The findings indicate that Muhammad Abduh emphasized educational reform through rationality, the rejection of taqlid, and the integration of religious and modern sciences within the Islamic educational curriculum. Meanwhile, Muhammad Iqbal emphasized the reconstruction of Islamic educational philosophy through the concept of khudi, which focuses on the development of self-awareness, creativity, and moral responsibility. The comparative analysis shows that both perspectives offer complementary approaches in constructing a more holistic paradigm of Islamic education. The integration of Abduh’s educational reform and Iqbal’s philosophical reconstruction provides a relevant conceptual framework for developing Islamic education capable of responding to modern challenges while preserving its spiritual and moral foundations.